EVALUATING THE INFLUENCE OF CURCUNIN ON BONE RESPONSE DURING TEETH DISPLACEMENT: AN EXPERMENTAL IN VIVO STUDY - NAWAF, ROKAN MOAWYIA; ALSULTAN, MUSTAFA MUATH (Journal of Duhok University, 2023)
Background and objectives: Orthodontic treatment attempts to improve people's quality of life. A complex and lengthy inflammatory process including simultaneous bone resorption and apposition is required. The length of the treatment process is the most common complaint of patients seeking during treatment. The purpose of this experimental study is to determine the effects of three weeks consumption of curcumin on the rate of orthodontic tooth movement, the level of serum calcium- phosphorous and histomorphometric analysis. Materials and methods: Twenty healthy male rabbits weighting 1.75 – 2 kg were used; the rabbits were divided in to two groups at random with each group consisting of ten rabbits. Both groups were subjected to orthodontic appliances with the study group receiving a daily dose of curcumin orally for 21 days. Results: The study group showed tooth movement more than the control group with a decrease in the level of serum calcium and an increase in the level of serum phosphorous, the histomorphometric analysis showed an increase in the number of osteoblasts in the tension side and an increase in the number of osteoclasts in the compression side.Conclusion: Consumption of curcumin improved the rate of orthodontic tooth movement